Quantification of circumferential, longitudinal, and radial global fractional shortening using steady‐state free precession cines: A comparison with tissue‐tracking strain and application in fabry disease. Issue 2 (13th March 2014) - Cheng‐Baron, June; Chow, Kelvin; Pagano, Joseph J.; Punithakumar, Kumaradevan; Paterson, D. Ian; Oudit, Gavin Y.; Thompson, Richard B.
<x xml:space="preserve">Abstract</x> Purpose Conventional calculation of myocardial strain requires tissue‐tracking. A surrogate for strain called global fractional shortening (GFS) is proposed based on changes in dimensions of endocardial and epicardial surfaces without tissue‐tracking. Methods Three‐dimensional endocardial and epicardial left ventricular surfaces traced at end‐diastole and end‐systole using conventional steady‐state free precession cine images were used to calculate GFScc (circumferential), GFSll (longitudinal), and GFSrr (radial) using fractional length changes in each direction over the heart surface. GFS values were validated using finite element models (FEM) and in vivo using tagging‐derived strains (εcc, εll, εrr) in patients with a wide range of ejection fraction (EF) and diagnosis (n = 32). GFS was also measured in 31 patients with Fabry disease and matched healthy controls. Results GFS values were within 3% of average FEM‐derived Lagrangian strains and had good agreement in vivo (GFScc = −14 ± 4%, εcc = −14 ± 4%, R2 = 0.85; GFSll = −12 ± 4%, εll = −12 ± 4%, R2 = 0.72; GFSrr = 46 ± 21%). εrr could not be measured reliably from tagging. Compared with healthy controls with matched EF, patients with Fabry disease had significantly increased GFScc (Endo) (−28 ± 3% versus −25 ± 2%), decreased GFScc(Epi) (−10 ± 2% versus −11 ± 2%) and decreased GFSll for all components. Conclusion GFS yields similar values to conventionally measured strains without requiring tissue‐tracking. Compared with controls, patients with Fabry disease have significant differences in several GFS components. Magn Reson Med 73:586–596, 2015. © 2014 Wiley Periodicals, Inc.